SiC nanowire in-situ modified ceramic matrix composite connecting fastener and preparation method thereof
Through the preparation method of SiC nanowire in-situ modified ceramic matrix composite material, the problem of poor performance of high-temperature alloy materials at high temperatures is solved, and efficient connection of CMC-SiC fasteners and improved material performance are achieved.
Patent Information
- Application Number
- CN202411882646.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing high-temperature alloy materials have poor tolerance, large mass, and mismatched thermal expansion coefficient at high temperatures, resulting in poor performance of fasteners at the connection parts of ceramic matrix composite materials.
SiC nanowire in situ modified ceramic matrix composite material is used to prepare connecting fasteners through steps such as heat treatment, interface layer deposition, catalyst solution impregnation and CVI deposition, establish a global load sharing mechanism, and enhance the toughness of the material through SiC nanowires.
It improves the connection efficiency of CMC-SiC fasteners, enhances the tensile and shear resistance of the material, improves the cohesion and density of the pyrolytic carbon layer, and reduces the preparation cost and cycle.
Smart Images

Figure CN119638466A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic-based composite materials, and in particular to a SiC nanowire in-situ modified ceramic-based composite material connecting fastener and a preparation method thereof. Background Art
[0002] In view of the application needs of CMC-SiC materials in aerospace, aviation, aeroengine, deep space exploration and other fields, CMC-SiC components are mostly large and complex thin-walled components with irregular shapes. In the process of forming and processing using traditional fiber integral weaving technology, there are problems such as poor mechanical properties of components in the bending area of woven fibers, the need to replace the entire component due to damage in small areas, poor maintainability, long preparation cycle and high preparation cost. Therefore, the use of disassembly and assembly processes to prepare large and complex CMC-SiC thin-walled components is a general technology that is given priority in integrated manufacturing, and is also the only way for this material and its components to achieve serialization, generalization and combination.
[0003] Practice has shown that in the integrated manufacturing process of disassembly and assembly, the connection parts of ceramic-based composite materials are the weakest links in the integrated assembly manufacturing components. The strength, temperature resistance and environmental adaptability of the fasteners at the connection will have a certain impact on the overall performance of the components. At present, the connection carriers for realizing the integrated assembly and manufacturing of CMC-SiC components mainly include two branches: metal materials represented by high-temperature alloys and inorganic non-metallic materials represented by CMC-SiC. Considering the problems of high-temperature alloy materials that have low temperature tolerance (<1100℃), large mass, and mismatched thermal expansion coefficients, CMC-SiC materials have gradually become the preferred material for connectors. Therefore, there is an urgent need for connection fasteners mainly made of two materials (C / SiC, SiC / SiC) and two types (bolts and screws). Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a SiC nanowire in-situ modified ceramic-based composite material connecting fastener and a preparation method thereof, so as to solve the problems of existing high-temperature alloy materials such as low temperature resistance (<1100°C), large mass, and mismatched thermal expansion coefficient.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A method for preparing a SiC nanowire in-situ modified ceramic matrix composite material connecting fastener comprises the following steps:
[0007] (1) firstly heat-treating the fiber preform, then performing CVD or CVI deposition using boron trichloride and ammonia or boron trichloride and ethylene as precursors to prepare an interface layer, then dipping in a catalyst solution, drying, and finally performing CVI deposition using trichloromethylsilane as a precursor to obtain a composite material preform;
[0008] (2) Firstly, the composite material preform obtained in step (1) is subjected to CVD or CVI deposition using silicon tetrachloride and ammonia as precursors to prepare a pre-processed sample, and then immersed in a precursor solution, dried, and then subjected to vacuum cracking treatment. Finally, silicon tetrachloride and ammonia are used as precursors again for CVI deposition, and then threads are processed to obtain.
[0009] The beneficial effects of the present invention are as follows: the SiC nanowire in-situ modified ceramic matrix composite fastener prepared by the present invention is composed of fibers, interfaces, SiC nanowires and a matrix, and a global load sharing mechanism is established. At the same time, the introduction of SiC nanowires can serve as a second reinforcement phase to enhance toughness together with the fibers, effectively improving the connection efficiency of CMC-SiC fasteners.
[0010] Furthermore, the fiber preform is a C fiber preform, including any one of a two-dimensional fiber cloth laminate, a three-dimensional needle punched preform and a fine-woven puncture preform.
[0011] Furthermore, before heat treating the fiber preform in step (1), the fiber preform is placed in acetone for cleaning.
[0012] Furthermore, the heat treatment temperature in step (1) is 400-600° C. and the time is 2-4 hours.
[0013] Preferably, the heat treatment temperature in step (1) is 500° C. and the time is 3 h.
[0014] Furthermore, in step (1), the conditions for CVD or CVI deposition using boron trichloride and ammonia or boron trichloride and ethylene as precursors are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of boron trichloride is 0.15-0.3 L / min, the flow rate of ammonia or ethylene is 0.25-0.5 L / min, the flow rate of argon is 0.6-2 L / min, the flow rate of hydrogen is 0.5-1 L / min, the pressure in the furnace is 2-5 kPa, the deposition temperature is 650-900° C., the deposition time is 10-50 h, and the thickness of the interface layer is 200-1500 nm.
[0015] Preferably, in step (1), the conditions for CVD or CVI deposition using boron trichloride and ammonia or boron trichloride and ethylene as precursors are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of boron trichloride is 0.225 L / min, the flow rate of ammonia or ethylene is 0.4 L / min, the flow rate of argon is 1.3 L / min, the flow rate of hydrogen is 0.75 L / min, the pressure in the furnace is 3.5 kPa, the deposition temperature is 750°C, the deposition time is 30 h, and the thickness of the interface layer is 1000 nm.
[0016] Furthermore, the interface layer is a PyC interface or a BN interface.
[0017] Furthermore, in step (1), the catalyst comprises any one of ferrocene, ferrophenylacetate, nickelocene, nickel acetate, nickel nitrate and nickel chloride; the mass ratio of the catalyst to water in the catalyst solution is (5-20): (80-95); the immersion time in the catalyst solution is 30-60 min; the drying temperature is 70-80° C. and the drying time is 3-5 h.
[0018] Preferably, the catalyst in step (1) comprises any one of ferrocene, ferrophenylacetate, nickelocene, nickel acetate, nickel nitrate and nickel chloride; the mass ratio of the catalyst to water in the catalyst solution is 10:900; the immersion time in the catalyst solution is 45 minutes; the drying temperature is 75° C. and the drying time is 4 hours.
[0019] Furthermore, the immersion environment pressure is -0.1 MPa.
[0020] Furthermore, in step (1), the conditions for CVI deposition using trichloromethylsilane as a precursor are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 2.5-10 L / min, the hydrogen carrier gas flow rate is 1.5-5 L / min, the hydrogen dilution gas flow rate is 2.5-5 L / min, the furnace pressure is 0.3-0.6 kPa, the deposition temperature is 700-1000° C., and the deposition time is 5-50 h.
[0021] Preferably, the conditions for CVI deposition using trichloromethylsilane as a precursor in step (1) are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 6 L / min, the hydrogen carrier gas flow rate is 3 L / min, the hydrogen dilution gas flow rate is 4 L / min, the furnace pressure is 0.45 kPa, the deposition temperature is 850°C, and the deposition time is 20 h.
[0022] The beneficial effect of adopting the above further technical solution is: the present invention adopts chemical vapor phase method and immerses the catalyst solution containing Fe or Ni to grow SiC nanowires, and can obtain SiC nanowire micro-nano modified-carbon fiber / pyrolytic carbon (SiC nw -C f / PyC) composite material preform can effectively improve the problems of poor mechanical properties in weak areas of C / C composite materials.
[0023] Further, in step (2), the conditions for CVD or CVI deposition using silicon tetrachloride and ammonia as precursors are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of silicon tetrachloride is 100-500 mL / min, the flow rate of ammonia is 150-1000 mL / min, the flow rate of argon is 300-2500 mL / min, the flow rate of hydrogen is 750-2500 mL / min, the pressure in the furnace is 1-5 kPa, the deposition temperature is 700-1100 ° C, the deposition time is 8-200 h, and the deposition is performed until the density of the composite material reaches 1.55-1.75 g / cm 3 .
[0024] Preferably, in step (2), the conditions for CVD or CVI deposition using silicon tetrachloride and ammonia as precursors are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of silicon tetrachloride is 300 mL / min, the flow rate of ammonia is 500 mL / min, the flow rate of argon is 1200 mL / min, the flow rate of hydrogen is 1200 mL / min, the pressure in the furnace is 3 kPa, the deposition temperature is 900 ° C, the deposition time is 50 h, and the deposition is carried out until the density of the composite material reaches 1.65 g / cm 3 .
[0025] Furthermore, in step (2), the mass ratio of the precursor material, the solvent and the catalyst in the precursor solution is 35-50:50-65:3-7; the precursor material is at least one of polycarbosilane, polysilazane, polyzirconate and polyborozirconate; the catalyst is at least one of ferrocene, ferrophenylacetate, nickelocene, nickel acetate, nickel nitrate and nickel chloride; the immersion time is 30-60 min, the drying temperature is 70-80° C., and the drying time is 3-5 h.
[0026] Preferably, in step (2), the mass ratio of the precursor material, the solvent and the catalyst in the precursor solution is 40:60:5; the precursor material is at least one of polycarbosilane, polysilazane, polyzirconate and polyborozirconate; the catalyst is at least one of ferrocene, ferrophenylacetate, nickelocene, nickel acetate, nickel nitrate and nickel chloride; the immersion time is 45 minutes, the drying temperature is 705°C, and the drying time is 4 hours.
[0027] Further, the solvent includes xylene, divinylbenzene or cyclohexane.
[0028] Furthermore, the immersion environment pressure is -0.1 MPa.
[0029] Furthermore, the conditions for vacuum cracking treatment in step (2) are: vacuum degree is 0.08-0.1MPa, first heating to 1200-1500°C at a heating rate of 3-10°C / min, keeping warm for 1-3h, then cooling to 500-700°C at a cooling rate of 3-10°C / min, and cooling with the furnace.
[0030] Preferably, the conditions for vacuum cracking treatment in step (2) are: vacuum degree is 0.09 MPa, first the temperature is increased to 1350°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, then the temperature is decreased to 600°C at a cooling rate of 5°C / min, and then cooled in the furnace.
[0031] The beneficial effect of adopting the above further technical solution is: the present invention adopts polymer conversion combined with high-temperature cracking method to in-situ self-grow SiC nanowires inside and on the surface of the sample, and at the same time, part of the polymer inside the composite is also converted into SiC matrix, which not only strengthens and toughens the thread teeth, but also helps to quickly densify.
[0032] Furthermore, in step (2), the conditions for CVI deposition using silicon tetrachloride and ammonia as precursors are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 2.5-10 L / min, the hydrogen carrier gas flow rate is 1.5-5 L / min, the hydrogen dilution gas flow rate is 2.5-5 L / min, the furnace pressure is 1-5 kPa, the deposition temperature is 700-1100° C., and the deposition time is 8-200 h.
[0033] Preferably, in step (2), the conditions for CVI deposition again using silicon tetrachloride and ammonia as precursors are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 6 L / min, the hydrogen carrier gas flow rate is 3 L / min, the hydrogen dilution gas flow rate is 4 L / min, the furnace pressure is 3 kPa, the deposition temperature is 900°C, and the deposition time is 50 h.
[0034] Furthermore, the density of the sample finally obtained in step (2) is 2.05-2.35 g / cm 3 , the open porosity is 10-15%.
[0035] A SiC nanowire in-situ modified ceramic-based composite material connecting fastener is prepared by adopting the preparation method.
[0036] The present invention has the following beneficial effects:
[0037] (1) In the ceramic-based composite fastener prepared by the present invention, SiC nanowires are non-directionally distributed in the composite material, and pyrolytic carbon is deposited in a ring shape around them. The SiC nanowires can serve as a second reinforcement phase and reinforce the C / C composite material together with the fibers; some SiC nanowires grow radially outward perpendicular to the fibers, which can effectively improve the interface bonding between the carbon fibers and the PyC matrix; in addition, the SiC nanowires are connected in series between PyC layers, which can not only reduce the defects of the pyrolytic carbon layer, but also enhance the cohesion of the pyrolytic carbon.
[0038] (2) The SiC nanowires in the present invention play a bridging role in the defects, which can effectively alleviate the crack propagation; the SiC nanowires play a filling role, which can repair the defects and enhance the load bearing capacity between the defects; the SiC nanowires are interspersed between the pyrolytic carbon matrix, which has a toughening and strengthening effect on the pyrolytic carbon; during the stress process, the SiC nanowires themselves will break and absorb the fracture energy, thereby improving the material's load-bearing capacity.
[0039] (3) The SiC nanowires grown in situ on the surface of the thread teeth of the composite material bolt prepared by the present invention can effectively bear the load. The energy released by resisting thread tooth missing and pull-off can be borne by the nanowires. The introduction of nanowires can also improve the density of the thread teeth and the studs, which is beneficial to improving the tensile and shear resistance of the bolts. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The present invention is a process roadmap for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener;
[0041] Figure 2 SiC is prepared in Example 1 of the present invention nw -C f Microscopic morphology of SiC nanowires in SiC nanowire-in-situ modified ceramic matrix composite fasteners, where (a) is SiC nanowires. nw -C f / PyC composite preform, (b) is a pre-processed sample with nanowires, (c) and (d) are SiC nanowire in-situ modified ceramic matrix composite fasteners;
[0042] Figure 3 This is a fracture analysis diagram of the SiC nanowire in-situ modified ceramic-based composite fastener obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0044] Embodiment 1:
[0045] A method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener (process route diagram as shown in FIG. Figure 1 As shown), comprising the following steps:
[0046] (1) Fiber preform pretreatment
[0047] A carbon fiber two-dimensional fiber cloth laminate was selected as the preform, and the fiber preform was placed in acetone for cleaning to remove surface contaminants. The cleaned fiber preform was then placed in a muffle furnace (air atmosphere) for heat treatment, the temperature was raised to 500°C, and after keeping the temperature for 3 hours, it was cooled with the furnace to remove the adhesive coating on the fiber surface.
[0048] (2) Interface layer preparation
[0049] The CVI process is used to prepare a PyC interface in the fiber preform after pretreatment in step (1) to prepare a composite material with weak interface bonding. The fiber preform material is hung on a sample rack supporting a vacuum furnace, and the fiber preform material is located at the center of the isothermal zone in the furnace. Boron trichloride, ethylene, diluent gas argon and catalytic gas hydrogen are introduced at the same time. The flow rate of boron trichloride is 0.225L / min, the flow rate of ethylene is 0.4L / min, the flow rate of argon is 1.3L / min, the flow rate of hydrogen is 0.75L / min, the pressure in the furnace is 3.5kPa, the deposition temperature is 750℃, the deposition time is 30h, and a preform with an interface layer thickness of 1000nm is obtained.
[0050] (3) Preparation of a preform containing a catalyst solution
[0051] First, 10% by mass of ferrocene and 90% by mass of deionized water are mixed and stirred at a speed of 500 rpm for 45 minutes to obtain a catalyst solution; then, a vacuum impregnation method is used to immerse the preform obtained after the CVI process in step (2) in the catalyst solution under a pressure of -0.1 MPa, and the mixture is taken out after being kept for 60 minutes, and dried at 70°C for 4 hours to obtain a preform containing the catalyst solution.
[0052] (4) Preparation of SiC nanowire modified-carbon fiber / pyrolytic carbon (SiC nw -C f / PyC) composite material preform
[0053] The preform containing the catalyst solution obtained in step (3) was deposited by the CVI process to generate SiC nanowires inside and on the surface thereof. The deposition conditions were as follows: the precursor was trichloromethylsilane, the diluent gas was argon, the catalytic gas was hydrogen, the argon flow rate was 6 L / min, the hydrogen carrier gas flow rate was 3 L / min, the hydrogen dilution gas flow rate was 4 L / min, the furnace pressure was 0.45 kPa, the deposition temperature was 850 ° C, the deposition time was 20 h, and SiC was obtained. nw -C f / PyC composite material preform.
[0054] (5) Preparation of matrix materials
[0055] The SiC obtained in step (4) by CVI processnw -C f / PyC composite material preforms are used to prepare dense Si3N4 matrix and coating inside and on the surface. The precursors are silicon tetrachloride and ammonia, the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of silicon tetrachloride is 300mL / min, the flow rate of ammonia is 500mL / min, the flow rate of argon is 1200mL / min, the flow rate of hydrogen is 1200mL / min, the pressure in the furnace is 3kPa, the deposition temperature is 900℃, the deposition time is 50h, and the deposition is carried out until the density of the composite material reaches 1.65g / cm 3 , obtain the base material, and cut the fasteners into strips and grind them into circles according to the size standards to obtain pre-processed samples.
[0056] (6) Preparation of Nanowires
[0057] First, polycarbosilane and xylene are mixed in a mass ratio of 40%:50%, and then ferrocene with a total mass fraction of 5% of polycarbosilane and xylene is added and stirred to obtain a precursor solution; then the pre-processed sample obtained in step (5) is immersed in the precursor solution under a -0.1MPa environment for vacuum impregnation, kept for 60 minutes, and then taken out and dried at 70°C for 4 hours; finally, the dried pre-processed sample is placed in a vacuum tube furnace to crack and grow nanowires, the vacuum degree in the furnace is 0.09MPa, and the cracking conditions are: first, the temperature is increased to 1350°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours, and then the temperature is decreased to 600°C at a cooling rate of 5°C / min, and then the temperature is cooled with the furnace. Argon is introduced as a protective atmosphere during the cracking process to obtain a pre-processed sample with nanowires.
[0058] (7) Preparation of SiC nanowire in-situ modified ceramic matrix composite fasteners
[0059] The SiC protective layer was deposited on the surface of the pre-processed sample with nanowires obtained in step (6) by CVI process. The deposition conditions were as follows: the precursors were silicon tetrachloride and ammonia, the diluent gas was argon, the catalytic gas was hydrogen, the argon flow rate was 6 L / min, the hydrogen carrier gas flow rate was 3 L / min, the hydrogen dilution gas flow rate was 4 L / min, the furnace pressure was 3 kPa, the deposition temperature was 900 °C, the deposition time was 50 h, and the density was 2.2 g / cm 3 , a pre-processed sample of nanowire reinforced ceramic matrix composite material with a porosity of 12% was opened, and then the screw, bolt, stud, nut and pin were processed according to the thread specification requirements to obtain SiC nanowire in-situ modified ceramic matrix composite connecting fasteners.
[0060] Embodiment 2:
[0061] A method for preparing a SiC nanowire in-situ modified ceramic matrix composite material connecting fastener comprises the following steps:
[0062] (1) Fiber preform pretreatment
[0063] A carbon fiber three-dimensional needle-punched preform was selected as the preform, and the fiber preform was placed in acetone for cleaning to remove surface contaminants. The cleaned fiber preform was then placed in a muffle furnace (air atmosphere) for heat treatment, the temperature was raised to 500°C, and after keeping the temperature for 3 hours, it was cooled with the furnace to remove the adhesive coating on the fiber surface.
[0064] (2) Interface layer preparation
[0065] The CVI process is used to prepare a PyC interface in the fiber preform after pretreatment in step (1) to prepare a composite material with weak interface bonding. The fiber preform material is hung on a sample rack supporting a vacuum furnace, and the fiber preform material is located at the center of the isothermal zone in the furnace. Boron trichloride, ethylene, diluent gas argon and catalytic gas hydrogen are introduced at the same time. The flow rate of boron trichloride is 0.225L / min, the flow rate of ethylene is 0.4L / min, the flow rate of argon is 1.3L / min, the flow rate of hydrogen is 0.75L / min, the pressure in the furnace is 3.5kPa, the deposition temperature is 900°C, and the deposition time is 25h to obtain a preform with an interface layer.
[0066] (3) Preparation of a preform containing a catalyst solution
[0067] First, 15% by mass of ferric phenylacetate and 85% by mass of deionized water are mixed and stirred at a speed of 500 rpm for 45 minutes to obtain a catalyst solution; then, a vacuum impregnation method is used to immerse the preform obtained after the CVI process in step (2) in the catalyst solution under a pressure of -0.1 MPa, and the mixture is taken out after being kept for 60 minutes, and dried at 70°C for 4 hours to obtain a preform containing the catalyst solution.
[0068] (4) Preparation of SiC nanowire modified-carbon fiber / pyrolytic carbon (SiC nw -C f / PyC) composite material preform
[0069] The preform containing the catalyst solution obtained in step (3) was deposited by CVI process to generate SiC nanowires inside and on the surface thereof. The deposition conditions were as follows: the precursor was trichloromethylsilane, the diluent gas was argon, the catalytic gas was hydrogen, the argon flow rate was 6 L / min, the hydrogen carrier gas flow rate was 3 L / min, the hydrogen dilution gas flow rate was 4 L / min, the furnace pressure was 0.45 kPa, the deposition temperature was 800 ° C, the deposition time was 25 h, and SiC was obtained. nw -C f / PyC composite material preform.
[0070] (5) Preparation of matrix materials
[0071] The SiC obtained in step (4) by CVI process nw -C f / PyC composite material preform and surface preparation of dense Si3N4 matrix and coating. The precursor is silicon tetrachloride and ammonia, the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of silicon tetrachloride is 300mL / min, the flow rate of ammonia is 500mL / min, the flow rate of argon is 1200mL / min, the flow rate of hydrogen is 1200mL / min, the pressure in the furnace is 3kPa, the deposition temperature is 1000℃, the deposition time is 50h, and the deposition is carried out until the density of the composite material reaches 1.65g / cm 3 , obtain the base material, and cut the fasteners into strips and grind them into circles according to the size standards to obtain pre-processed samples.
[0072] (6) Preparation of Nanowires
[0073] First, polycarbosilane and divinylbenzene are mixed in a mass ratio of 45%:55%, and then ferric phenylacetate with a total mass fraction of 5% of polycarbosilane and xylene is added and stirred to obtain a precursor solution; then the pre-processed sample obtained in step (5) is immersed in the precursor solution under a -0.1MPa environment for vacuum impregnation, kept for 60 minutes, and then taken out and dried at 70°C for 4 hours; finally, the dried pre-processed sample is placed in a vacuum tube furnace to crack and grow nanowires, the vacuum degree in the furnace is 0.09MPa, and the cracking conditions are: first, the temperature is increased to 1500°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours, and then the temperature is decreased to 600°C at a cooling rate of 5°C / min, and then the temperature is cooled with the furnace. Argon is introduced as a protective atmosphere during the cracking process to obtain a pre-processed sample with nanowires.
[0074] (7) Preparation of SiC nanowire in-situ modified ceramic matrix composite fasteners
[0075] A SiC protective layer is deposited on the surface of the pre-processed sample with nanowires obtained in step (6) using the CVI process. The deposition conditions are as follows: the precursors are silicon tetrachloride and ammonia, the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 6 L / min, the hydrogen carrier gas flow rate is 3 L / min, the hydrogen dilution gas flow rate is 4 L / min, the furnace pressure is 3 kPa, the deposition temperature is 800°C, and the deposition time is 50 h. A pre-processed sample of nanowire-reinforced ceramic-based composite materials is obtained. Then, screws, bolts, studs, nuts and pins are processed according to thread specifications to obtain SiC nanowire in-situ modified ceramic-based composite connecting fasteners.
[0076] Embodiment 3:
[0077] A method for preparing a SiC nanowire in-situ modified ceramic matrix composite material connecting fastener comprises the following steps:
[0078] (1) Fiber preform pretreatment
[0079] A carbon fiber fine-woven puncture preform was selected as the preform, and the fiber preform was placed in acetone for cleaning to remove surface contaminants. The cleaned fiber preform was then placed in a muffle furnace (air atmosphere) for heat treatment, the temperature was raised to 500°C, and after keeping the temperature for 3 hours, it was cooled with the furnace to remove the adhesive coating on the fiber surface.
[0080] (2) Interface layer preparation
[0081] The CVI process is used to prepare a PyC interface in the fiber preform after pretreatment in step (1) to prepare a composite material with weak interface bonding. The fiber preform material is hung on a sample rack supporting a vacuum furnace, and the fiber preform material is located at the center of the isothermal zone in the furnace. Boron trichloride, ethylene, diluent gas argon and catalytic gas hydrogen are introduced at the same time. The flow rate of boron trichloride is 0.225L / min, the flow rate of ethylene is 0.4L / min, the flow rate of argon is 1.3L / min, the flow rate of hydrogen is 0.75L / min, the pressure in the furnace is 3.5kPa, the deposition temperature is 700°C, and the deposition time is 35h to obtain a preform with an interface layer.
[0082] (3) Preparation of a preform containing a catalyst solution
[0083] First, nickel acetate with a mass fraction of 5% and deionized water with a mass fraction of 95% are mixed and stirred at a speed of 500 rpm for 45 minutes to obtain a catalyst solution; then, the preform obtained after the CVI process in step (2) is immersed in the catalyst solution under a pressure of -0.1 MPa by a vacuum impregnation method, kept for 60 minutes, then taken out, and dried at 70°C for 4 hours to obtain a preform containing the catalyst solution.
[0084] (4) Preparation of SiC nanowire modified-carbon fiber / pyrolytic carbon (SiC nw -C f / PyC) composite material preform
[0085] The preform containing the catalyst solution obtained in step (3) was deposited by the CVI process to generate SiC nanowires inside and on the surface thereof. The deposition conditions were as follows: the precursor was trichloromethylsilane, the diluent gas was argon, the catalytic gas was hydrogen, the argon flow rate was 6 L / min, the hydrogen carrier gas flow rate was 3 L / min, the hydrogen dilution gas flow rate was 4 L / min, the furnace pressure was 0.45 kPa, the deposition temperature was 900 ° C, the deposition time was 20 h, and SiC was obtained. nw -C f / PyC composite material preform.
[0086] (5) Preparation of matrix materials
[0087] The SiC obtained in step (4) by CVI process nw -C f / PyC composite material preforms to prepare dense Si3N4 matrix and coating inside and on the surface. The precursors are silicon tetrachloride and ammonia, the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of silicon tetrachloride is 300mL / min, the flow rate of ammonia is 500mL / min, the flow rate of argon is 1200mL / min, the flow rate of hydrogen is 1200mL / min, the pressure in the furnace is 3kPa, the deposition temperature is 800℃, the deposition time is 50h, and the deposition is carried out until the density of the composite material reaches 1.65g / cm 3 , obtain the base material, and cut the fasteners into strips and grind them into circles according to the size standards to obtain pre-processed samples.
[0088] (6) Preparation of Nanowires
[0089] First, polyzirconate carbene and cyclohexane are mixed in a mass ratio of 35%:65%, and then polycarbosilane and nickel acetate with a total mass fraction of 5% of xylene are added, and the mixture is stirred evenly to obtain a precursor solution; then, the pre-processed sample obtained in step (5) is immersed in the precursor solution under a -0.1MPa environment for vacuum impregnation, kept for 60 minutes, and then taken out and dried at 70°C for 4 hours; finally, the dried pre-processed sample is placed in a vacuum tube furnace to crack and grow nanowires, the vacuum degree in the furnace is 0.09MPa, and the cracking conditions are: first, the temperature is increased to 1200°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours, and then the temperature is decreased to 600°C at a cooling rate of 5°C / min, and then the temperature is cooled with the furnace. Argon gas is introduced as a protective atmosphere during the cracking process to obtain a pre-processed sample with nanowires.
[0090] (7) Preparation of SiC nanowire in-situ modified ceramic matrix composite fasteners
[0091] A SiC protective layer is deposited on the surface of the pre-processed sample with nanowires obtained in step (6) using the CVI process. The deposition conditions are as follows: the precursors are silicon tetrachloride and ammonia, the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 6 L / min, the hydrogen carrier gas flow rate is 3 L / min, the hydrogen dilution gas flow rate is 4 L / min, the furnace pressure is 3 kPa, the deposition temperature is 1000°C, and the deposition time is 50 h. A pre-processed sample of nanowire-reinforced ceramic-based composite materials is obtained. Then, screws, bolts, studs, nuts and pins are processed according to thread specifications to obtain SiC nanowire in-situ modified ceramic-based composite connecting fasteners.
[0092] Test example:
[0093] (1) The SiC obtained in step (4) of Example 1 nw -C f The microstructure of the SiC nanowires in the SiC nanowire-in-situ modified ceramic matrix composite fastener was observed by scanning electron microscope. The experimental results are as follows: Figure 2 shown.
[0094] Figure 2 Figure (a) shows SiC nanowires grown on the surface and inside of a carbon fiber / pyrolytic carbon composite material preform after a pyrolytic carbon interface layer is prepared on a carbon fiber preform and the catalyst is impregnated by the CVI method. As shown in the figure, it can be observed that SiC nanowires grow radially and perpendicularly to the fiber along the outer diameter of the carbon fiber. The nanowires are curled and can effectively improve the cross-sectional bonding between the carbon fiber and the PyC matrix; in addition, SiC nanowires are connected in series between PyC layers, which can not only reduce the defects between the pyrolytic carbon layers, but also increase the cohesion of the pyrolytic carbon.
[0095] Figure 2 Figure (b) shows the morphology of SiC nanowires grown inside a semi-densified composite material by polymer conversion combined with high-temperature pyrolysis. It can be observed that the SiC nanowire layer is wrapped between the fiber bundles on which the SiC matrix has been deposited. The SiC nanowires play a filling role, can repair defects, enhance the load-bearing capacity between defects, and have a toughening effect.
[0096] Figure 2 Figure (c) shows SiC nanowires observed at the top and bottom of the thread after processing. This shows that the SiC nanowires have good growth effect and strong permeability, which can strengthen the bolt thread. The energy released to resist thread missing and pull-off can be borne by the nanowires. The introduction of nanowires can also improve the density of the thread and the bolt, which is beneficial to improving the tensile and shear resistance of the bolt.
[0097] Figure 2 The middle figure (d) is an enlarged morphology of the SiC nanowires at the thread teeth, showing that the nanowires are linear in morphology. The bent shape of the nanowires further demonstrates their good toughness.
[0098] (2) The fracture structure of the SiC nanowire in-situ modified ceramic matrix composite fastener obtained in Example 1 was characterized. The experimental results are as follows: Figure 3 shown.
[0099] according to Figure 3 As shown in Figures (a) to (c), the prepared SiC nanowires fill the inter-bundle pores of the sample well. Figure 3As can be seen from Figure (d), the growth of SiC nanowires on the surface of the sample did not affect the effective penetration of the SiC matrix in the later stage, nor did it cause crusting on the surface of the sample. Figure 3 It shows that the nanowire preparation process of the present invention can effectively improve the performance of fasteners. The SiC nanowires grown in situ on the surface of the bolt thread teeth can effectively bear the load. The energy released by resisting thread tooth missing and pull-off can be borne by the nanowires. The introduction of nanowires can also improve the compactness of the thread teeth and studs, which is beneficial to improving the tensile and shear resistance of the bolts. At the same time, the polymer conversion combined with the high-temperature pyrolysis method to prepare nanowires can also generate part of the SiC matrix, which helps to improve the densification preparation of the sample (SiC nanowires and SiC matrix are jointly enhanced), effectively reduce the densification deposition furnaces, and save costs.
[0100] (3) The room temperature tensile strength and shear strength of the M6 and M8 bolts processed in the SiC nanowire in-situ modified ceramic matrix composite material prepared in Example 1 were characterized. The experimental results are shown in Table 1.
[0101] Table 1 Room temperature tensile strength and shear strength of M6 and M8 bolts obtained in Example 1 of the present invention
[0102]
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener, characterized in that: The following steps are involved: (1) firstly heat-treating the fiber preform, then performing CVD or CVI deposition using boron trichloride and ammonia or boron trichloride and ethylene as precursors to prepare an interface layer, then dipping in a catalyst solution, drying, and finally performing CVI deposition using trichloromethylsilane as a precursor to obtain a composite material preform; (2) Firstly, the composite material preform obtained in step (1) is subjected to CVD or CVI deposition using silicon tetrachloride and ammonia as precursors to prepare a pre-processed sample, and then immersed in a precursor solution, dried, and then subjected to vacuum cracking treatment. Finally, silicon tetrachloride and ammonia are used as precursors again for CVI deposition, and then threads are processed to obtain.
2. The method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The heat treatment temperature in step (1) is 400-600° C. and the time is 2-4 hours.
3. The method for preparing the SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The conditions for CVD or CVI deposition using boron trichloride and ammonia or boron trichloride and ethylene as precursors in step (1) are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of boron trichloride is 0.15-0.3 L / min, the flow rate of ammonia or ethylene is 0.25-0.5 L / min, the flow rate of argon is 0.6-2 L / min, the flow rate of hydrogen is 0.5-1 L / min, the pressure in the furnace is 2-5 kPa, the deposition temperature is 650-900° C., the deposition time is 10-50 h, and the thickness of the interface layer is 200-1500 nm.
4. The method for preparing the SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The catalyst in step (1) comprises any one of ferrocene, ferrophenylacetate, nickelocene, nickel acetate, nickel nitrate and nickel chloride; the mass ratio of the catalyst to water in the catalyst solution is (5-20): (80-95); the immersion time in the catalyst solution is 30-60 minutes; the drying temperature is 70-80°C and the drying time is 3-5 hours.
5. The method for preparing the SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The conditions for CVI deposition using trichloromethylsilane as a precursor in step (1) are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 2.5-10 L / min, the hydrogen carrier gas flow rate is 1.5-5 L / min, the hydrogen dilution gas flow rate is 2.5-5 L / min, the furnace pressure is 0.3-0.6 kPa, the deposition temperature is 700-1000° C., and the deposition time is 5-50 h.
6. The method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The conditions for CVD or CVI deposition using silicon tetrachloride and ammonia as precursors in step (2) are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the flow rate of silicon tetrachloride is 100-500 mL / min, the flow rate of ammonia is 150-1000 mL / min, the flow rate of argon is 300-2500 mL / min, the flow rate of hydrogen is 750-2500 mL / min, the pressure in the furnace is 1-5 kPa, the deposition temperature is 700-1100° C., the deposition time is 8-200 h, and the deposition is performed until the density of the composite material reaches 1.55-1.75 g / cm 3 .
7. The method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: In the step (2), the mass ratio of the precursor material, the solvent and the catalyst in the precursor solution is 35-50:50-65:3-7; the precursor material is at least one of polycarbosilane, polysilazane, polyzirconate and polyborozirconate; the catalyst is at least one of ferrocene, ferrophenylacetate, nickelocene, nickel acetate, nickel nitrate and nickel chloride; the immersion time is 30-60 minutes, the drying temperature is 70-80°C, and the drying time is 3-5 hours.
8. The method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The conditions for the vacuum cracking treatment in step (2) are: the vacuum degree is 0.08-0.1 MPa, the temperature is first increased to 1200-1500°C at a heating rate of 3-10°C / min, kept at this temperature for 1-3 hours, then cooled to 500-700°C at a cooling rate of 3-10°C / min, and then cooled with the furnace.
9. The method for preparing a SiC nanowire in-situ modified ceramic matrix composite fastener according to claim 1, characterized in that: The conditions for CVI deposition again using silicon tetrachloride and ammonia as precursors in the step (2) are as follows: the diluent gas is argon, the catalytic gas is hydrogen, the argon flow rate is 2.5-10 L / min, the hydrogen carrier gas flow rate is 1.5-5 L / min, the hydrogen dilution gas flow rate is 2.5-5 L / min, the furnace pressure is 1-5 kPa, the deposition temperature is 700-1100° C., and the deposition time is 8-200 h.
10. A SiC nanowire in-situ modified ceramic matrix composite fastener, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing ceramic matrix composite material through SiC nano-wire modified ceramic matrix composite material interface
CN105237021A
Multilayer ceramic-based composite material for aero-engine thermal structural member and preparation method thereof
CN113735604A
Preparation method of whisker reinforced ceramic matrix composite connecting fastener
CN117865708A
Preparation method of nano-reinforced ceramic matrix composite fastener
CN117964389A
Preparation method for two-dimensional silicon carbide / silicon carbide composite material bar and connecting piece
WO2023060907A1